Ischemic stroke in a pediatric patient: complication of the course of COVID-19 (clinical case and literature review) - A. M. Shchetinina; V. P. Ivanov; A. V. Kim; G. G. Ivanova; V. A. Malko; T. M. Alekseeva (Русский журнал детской неврологии)
Recently, there is a growing number of publications about the complicated course of the COVID-19 in children. The literature describes only a few cases of acute cerebrovascular diseases. In the case described in this paper, an 11‑year-old boy presented with COVID-19 complicated by an ischemic stroke. Moderate ischemic stroke (pedNIHSS 14 points) occurred on the 7th day after infection with the SARS-CoV-2 and the background of the multisystem inflammatory syndrome. It has started with the left hemiplegia, hemianesthesia, central-type facial moderate palsy, and pseudobulbar palsy. Focal brain ischemia in the right hemisphere brain and occlusion of the right middle cerebral artery was confirmed by neuroimaging data. The treatment observed regression of neurological symptoms: there were minimal movements in his left arm and leg, facial muscles, also improved gulping and speech. After 1.5 months, the stroke was provided clinical examination: no markers predisposing to hypercoagulability or a prothrombotic state, as well as markers of systemic diseases. According to neuroimaging data, was occurred recanalization of occluded middle cerebral artery, was postischemic changes. This case shows the possibility of stroke against the background of COVID-19 in children without somatic problems and makes the doctor more vigilant during the treatment of COVID-19.